Advances in Salivary Diagnostics 2015
DOI: 10.1007/978-3-662-45399-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Using Saliva Secretions to Model Disease Progression

Abstract: IntroductionOver the decades, biological modeling has been used to study disease progression in numerous types of carcinomas. To date, no one model can completely predict cancer progression. Consequently, there are a plethora of different types of models for numerous carcinomas. Additionally, cancer modeling lacks an in vivo system that refl ects disease changes in a "real-time" approach.Saliva is a complex and dynamic biological fl uid, which over the years has been recognized for the numerous functions it pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Agha-Hosseini et al found that salivary and serum levels of CA15-3 were significantly higher in cancer patients, with a significant positive correlation between serum and saliva CA15-3 concentrations ( 24 ). Streckfus et al also reported a moderate correlation between salivary and serum CA15-3 concentration with ELISA ( 18 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Agha-Hosseini et al found that salivary and serum levels of CA15-3 were significantly higher in cancer patients, with a significant positive correlation between serum and saliva CA15-3 concentrations ( 24 ). Streckfus et al also reported a moderate correlation between salivary and serum CA15-3 concentration with ELISA ( 18 ).…”
Section: Discussionmentioning
confidence: 98%
“…The proposed hypothesis is that active transport of proteins into saliva by the salivary glandular epithelium could explain the presence of membrane-bound proteins such as CA15-3. In breast cancer patients, there would be an overabundance of various bioactive proteins associated with the rapid, abnormal growth of the neoplasm, which in turn could produce a response in the salivary glands (18). Further studies are necessary to better understand the regulatory mechanisms of elevated salivary CA15-3 in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the salivary composition can be influenced by the collection time (as cortisol secretion peak between 06:00 to 08:00 a.m.), collection methods (stimulated or not), current medical treatments, the presence of comorbidities or oral inflammation [ 11 , 12 ]. In this review, for example, the time of sampling is not always specified in the included studies ( n = 10/18), as well as the volume of saliva that was collected, varying from 1 to 4 mL when specified.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is also comparable to human serum metabolomes in terms of chemical complexity and abundance of metabolites [ 9 , 12 ]. Also, vs. of saliva could be an alternative to vs. using blood or its derived products, without being invasive and stressful for the patient and not requiring a more complex storage mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation